An unusual case of constriction ring dystocia - Bhati, Balgopal Singh; Patidar, Arti; Kori, Archana; Bhati, Indra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We present here an unusual case of constriction ring dystocia. In the case during intra-partum abdominal contour look like Bandl’s retraction ring but on cesarean section identified the constriction ring of uterine myometrium strangling the fetal forehead and face.